Pathological Role of Unsaturated Aldehyde Acrolein in Diabetic Retinopathy - Murata, Miyuki; Noda, Kousuke; Ishida, Susumu (Frontiers in Immunology, 2020)
With increasing prevalence of diabetes and a progressively aging society, diabetic retinopathy is emerging as one of the global leading causes of blindness. Recent studies have shown that vascular endothelial growth factor (VEGF) plays a central role in the pathogenesis of diabetic retinopathy and anti-VEGF agents have become the first-line therapy for the vision-threatening disease. However, recent studies have also demonstrated that diabetic retinopathy is a multifactorial disease and that VEGF-independent mechanism(s) also underlie much of the pathological changes in diabetic retinopathy. Acrolein is a highly reactive unsaturated aldehyde and is implicated in protein dysfunction. As acrolein is common in air pollutants, previous studies have focused on it as an exogenous causative factor, for instance, in the development of respiratory diseases. However, it has been discovered that acrolein is also endogenously produced and induces cell toxicity and oxidative stress in the body. In addition, accumulating evidence suggests that acrolein and/or acrolein-conjugated proteins are associated with the molecular mechanisms in diabetic retinopathy. This review summarizes the pathological roles and mechanisms of endogenous acrolein production in the pathogenesis of diabetic retinopathy.